Pemanfaatan Mikrolaga Chlorella sp Yang Diimmobilisasi Dalam Proses Penyisihan Logam Cr Pada Limbah Cair Industri Elektroplating - Ayu Eka Putri; Shinta Elystia; Edward HS (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The presence of Chromium (Cr) in electroplating wastewater is a major environmental problem. That toxicity and non-biodegradable where should be eliminated from water. Chlorella sp immobilized in calcium alginate is one of technology that can reduce the concentration of Cr in the electroplating wastewater quickly and without produced sludge. The data were analyzed using AAS on variation cell density in alga beads (0; 1,53x108; 1,76x107; 1,54x106 cells / beads) and contact time (0, 12, 24, 36 and 48 hours). The result showed that the highest removal efficiency of Cr occured at cell density 1,54x106 cells/beads and contact time 48 hours with efficiency of 52,04%.Keywords: biosorption, microalgae, Chlorella sp, cell density, contact time, Cr, electroplating wastewater